Developing creative content for games - Johnson, Greg, ....- (Boca Raton : Taylor & Francis/CRC, 2019)
This book provides readers with a solid understanding of game development, design, narrative, charaterization, plot, back story and world creation elements that are crucial for game writers and designers as they create a detailed world setting, adventure, characters, narrative and plot suitable for possible publication. Game design and development issues such as writing for games, emergent complexity, risk reward systems, competitive and cooperative game play will be investigated, analyzed and critiqued. Examples will be used to highlight and explain the various concepts involved and how the game development process works. Key Features •Provides the critical skills any good game designer should have, such as narrative, characterization, progression, challenges, world building, plot, and rewards •Using a hands-on, learn-by-doing approach, this book teaches prospective game designers how to excel in creating their own worlds and adventures without having to learn any programming or technical computer skills •Includes clear and concise chapter objectives, chapter overviews, examples, case studies, key terms and multiple in-depth analyses •Multiple case studies are provided and thoroughly analyzed so that readers will be familiar with the concepts and methodologies involved in each task •Over the course of the book, readers will develop a professional level asset for inclusion in a portfolio of work suitable for submitting to job applications
Keywords: Computer games - design; Electronic games - design